ダイ 28 ジ ナンキョク チイキ カンソク タイ ニ ヨル ナンキョク キコウ ヘンドウ ケンキュウ (ACR) カンソク ホウコク - 山内, 恭; ヤマノウチ, タカシ; 高部, 広昭; タカベ, ヒロアキ; Yamanouchi, Takashi; Takabe, Hiroaki (1989)
P(論文) 日本南極地域観測隊では, 第28次観測隊(1987年)より5ヵ年計画で「南極域における気候変動に関する総合研究(ACR)」を開始した。これは, 気候変動国際協同観測計画(WCRP)の中で, 南極の部分を担うもので, 南極における気候変動の実態を知り, 全地球規模の気候に対する南極の果たす役割を明らかにしようというものである。南極大気状態の年々変動と, 海氷-大気の相互作用, 氷床・棚氷変動, 氷床コア解析を重点課題としている。第28次観測隊では, 大気状態の年々変動をテーマに, 3本柱の観測を行った。1)雲の分布と放射では, 気象衛星NOAAによる観測から, 雲の分布や海氷の分布特性を求めた。地上における放射観測からは雲の情報を得, また雲の放射収支に対する影響を調べた。放射観測を衛星データと対比させることで, 衛星データ解釈の一助とした。2)広域気象観測ということで, あすか観測拠点で地上気象観測を始めると共に, 無人気象観測の展開に備え, みずほ基地を中心に無人気象観測機器のテストを行った。さらに, 3)微量成分モニタリングとして, CO_2濃度の連続測定やオゾンの観測(定常気象部門と共同)を行った。 The Japanese Antarctic Research Expedition (JARE) has started the 5-year project of "Antarctic Climate Research (ACR)" from JARE-28 in 1987. This project covers the field of Antarctica among the "World Climate Research Program (WCRP)", and aims at knowing the climate change in the Antarctic and clarifying the role of Antarctica in the global climate. Interannual variation of Antarctic atmosphere and air-sea ice interaction are set as the main subjects. In JARE-28,3 major items of observation were carried out under the subject of interannual variation of Antarctic atmosphere. 1) Cloud-radiation climatology : Cloud and sea ice distributions were observed by the NOAA satellite. Radiation measurements were made at the surface to obtain cloud information and to know the effect of clouds on the surface radiation budget. The surface radiation measurements are compared with satellite data to interpret the meanings of the satellite data. 2) Extention of meteorological observing area : The surface synoptic observation was started the newly established Asuka Camp and automatic weather stations were tested at Mizuho Station. 3) Monitoring of minor constituents : Continuous measurements of atmospheric CO_2 content and ozone observations were made. departmental bulletin paper